Efficient nitrogen removal in a total floc sludge system from domestic wastewater with low C/N: High anammox nitrogen removal contribution driven by endogenous partial denitrification. (June 2023) - Shang, Taotao; Zhu, Xiaorong; Gong, Xiaofei; Guo, Jingwen; Li, Xiyao; Zhang, Qiong; Peng, Yongzhen
Graphical abstract: Highlights: Endogenous partial denitrification boosted anammox with sustainable nitrification. Ca. Brocadia was enriched (0.92%) in a total floc sludge system under low C/N. Anammox nitrogen removal contribution rose to 78% during the anoxic stage of AOA. Inf.TIN and Eff.TIN were 51.5 mg/L and 8.5 mg/L respectively under low C/N (3.1). Abstract: Since unsustainable partial nitrification prone to unstable nitrogen removal rates, cultivation and enrichment of AnAOB, further improve autotrophic nitrogen removal contribution have been challenges in the mainstream anammox process. This study proposed a new strategy to enrich AnAOB motivated by endogenous partial denitrification (EPD) in total floc sludge system through the AOA process with sustainable nitrification. The results showed that in the presence of NH4 + and NO3 – at the anoxic stage of N-EPDA, Ca. Brocadia was enriched (0.005%→0.92%) in floc sludge via internal carbon source metabolism of EPD. The C/N and temperature of N-EPDA were also optimized to achieve higher activities of EPD and anammox. The N-EPDA was operated at low C/N ratio (3.1) with anammox nitrogen removal contribution of 78% during the anoxic stage, Eff.TIN of 8.3 mg/L and NRE of 83.5% during phase III, achieved efficient autotrophic nitrogen removal and AnAOB enrichment in the absence of partial nitrification.